Progress of Chinese Medicine in Regulating Altered Lipid Metabolism in Renal Fibrosis - Ma, Liang; Yu, Xiaoyong (Journal of Contemporary Medical Practice, 2025)
Renal fibrosis leads to progressive impairment of renal structure and function, which is a common pathologic impairment. There are few interventions targeting the mechanisms of fibrosis that can delay renal decompensation in patients. This review highlights the potential “antibiotic” of lipid metabolism and lipoproteins in ameliorating renal fibrosis, some representative targets and several other metabolic modulators with anti-fibrotic effects in the kidney, as well as the roles of fatty acid oxidation, lipids, and lipoprotein synthesis and catabolism in the prophylactic treatment of fibrosis. We describe the effects of lipid abnormalities on renal fibrosis and the renal pathophysiological lesions caused by lipid abnormalities, summarize the enzymes, transporter proteins, and transcription factors that contribute to the dysregulation of lipid metabolism in renal fibrosis, and discuss their roles in renal fibrosis. We summarized the renal protective effects of TCM monomers and TCM combinations mediating the pathways related to lipid metabolism flocculation, and made a review of them, aiming to provide theoretical basis for the drug development, basic research and clinical application of TCM in the prevention and treatment of renal fibrosis.